Obstructed Bochdalek hernia: a rare presentation of congenital diaphragmatic hernia in adulthood - N., Vikranth Suresh; P. N., Sreeramulu; Savagave, Shivaprasad Gangadhar; Vogu, Sundeep (International Surgery Journal, 2019)
Congenital diaphragmatic hernia (CDH) is usually diagnosed antenatally or during the initial few hours of life in newborns who present with respiratory distress. CDH presenting with intestinal obstruction in adulthood is very rare. We report a case of 28 year old male, who presented to emergency department, with acute onset of abdominal pain and breathlessness since 2 days. Patient was investigated and diagnosed to have Bochdalek hernia (BH), with herniation of intra-abdominal contents to thorax through the defect (3.5×4.5 cms) in postero-lateral aspect of left hemi-diaphragm with obstructive features of bowel. Patient underwent emergency exploratory laparotomy with reduction of contents and hernia repair. Patient recovered and remains well. High suspicion of BH should be done when patient presents with abdominal and respiratory symptoms even though it is very rare in adults.